2020
DOI: 10.1182/blood-2020-141940
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of CD19 CAR T-Cells for Pediatric Relapsed Acute Lymphoblastic Leukemia with Active CNS Involvement

Abstract: Background: CAR T cells targeting CD19 are approved for patients with relapsed or refractory acute lymphoblastic leukemia (ALL), failing two or more prior therapies. The central nervous system (CNS) is a known sanctuary site of ALL. Despite observations of CAR T-cells trafficking to the CNS in patients, most clinical trials excluded patients with active CNS leukemia, partially for concerns of neurotoxicity. Methods: We conducted an international retrospective study of patients who were referred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…32 Smaller institutional studies have shown efficacy and tolerability for patients with CNS disease, and commercial use of tisagenlecleucel for these patients continues to expand. 24,26 The data presented here further supports feasibility of treating patients with CNS leukemia with tisagenlecleucel without excess CRS or neurotoxicity. These results are consistent with another report of adult patients with CNS lymphoma who received tisagenlecleucel without evidence of greater than grade 1 neurotoxicity.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…32 Smaller institutional studies have shown efficacy and tolerability for patients with CNS disease, and commercial use of tisagenlecleucel for these patients continues to expand. 24,26 The data presented here further supports feasibility of treating patients with CNS leukemia with tisagenlecleucel without excess CRS or neurotoxicity. These results are consistent with another report of adult patients with CNS lymphoma who received tisagenlecleucel without evidence of greater than grade 1 neurotoxicity.…”
Section: Discussionsupporting
confidence: 71%
“…13 Another report of 27 pediatric patients described a higher rate of neurotoxicity in patients with CNS disease prior to lymphodepletion, although this cohort included a combination of patients who received either a 41BB or CD28z based CAR construct. 24 However, a report on the infusion of 7 patients with tisagenlecleucel who had isolated EM disease (negative or BM disease of <1%) demonstrated no increased neurotoxicity and achievement of a complete response (CR) in all patients. 25 Patients receiving either CTL019 and CTL119 for relapsed CNS disease similarly show clearance of CNS disease without increased risk of neurotoxicity and similar survival rates compared to patients without CNS disease at infusion.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, subsequent experience has not borne out this concern, and patients with CNS involvement do not appear to have markedly higher rates of neurotoxicity. [56][57][58][59] While the presence of CNS disease does not ipso facto indicate a higher risk of neurotoxicity, a relatively higher burden of it does appear to increase the risk of neurotoxicity, 57,59 and as such, strategies to reduce CNS disease burden are warranted in this population. Moreover, children with CNS disease (either with or without marrow involvement) have been found to have comparable long-term OS and EFS to children with marrow disease only, and are able to achieve remission at comparable rates .…”
Section: Cns Diseasementioning
confidence: 99%